The knowledge, attitudes, and perceptions towards a plant-based dietary pattern: a survey of obstetrician-gynecologists - Landry, Matthew J.; Ward, Catherine P.; Koh, Linda M.; Gardner, Christopher D. (Frontiers in Nutrition, 2024)
Background Obstetricians-gynecologists (OB/GYNs) play a critical role for their pregnant patients during their perinatal period, but research on OB/GYNs knowledge, attitudes, and perceptions regarding plant-based dietary patterns (PBDP) and how this may influence recommendations to patients is lacking. An online cross-sectional survey was conducted to examine OB/GYN’s knowledge, attitudes, and perceptions towards a PBDP. Methods Postcards were mailed in June 2023 to a convenience sample of 5,000 OB/GYNs across the US using a mailing list provided by the American College of Obstetricians and Gynecologists. Postcards had a brief study description and a QR code that linked to an online survey asking questions about demographics, behavior (e.g., nutritional habits), and other factors that may influence knowledge, attitudes, and perceptions towards a PBDP for their patients. Results Ninety-six OB/GYNs completed the full questionnaire (~2% response rate). Most (92%) felt that it is within an OB/GYN’s role to incorporate nutrition education and counseling within practice. However, 72% felt inadequately trained to discuss nutrition and diet-related issues with patients. Despite a perceived lack of nutrition training, 86% reported that a PBDP was safe and health-promoting, and 81% reported that a well-planned PBDP could adequately meet all nutritional needs of pregnant and lactating patients. Conclusion Findings suggest that OB/GYNs are generally knowledgeable about the components and health benefits of a plant-based diets. However, nutrient adequacy misconceptions and lack of sufficient training to discuss nutrition with patients may result in OB/GYNs not recommending PBDPs to patients. These findings underscore the need to enhance OB/GYN graduate medical education and training by integrating education on PBDPs, therefore improving a clinician’s ability to confidently and effectively counsel pregnant persons on this aspect of perinatal care.